Evaluasi Persiapan Pelaksanaan Program Sistem Administrasi Perkantoran Maya (Simaya) di Sekretariat Daerah Provinsi Sumatera Barat - Mercya Vaguita (Journal of Education on Social Science (JESS), 2018)
The implementation of Virtual Office Administration System (SiMAYA) in Secretariat Office of West Sumatera Province still faced various obstacles, such as lack of regulation, limited of human resources, and so on. The purpose of this study was to determine the determinant factors in the implementation of SIMAYA program, and efforts made in overcoming the problem. This study was conducted through a qualitative research using descriptive method. The informants of this study were determined through purposive technique. The data of this study were collected through observation, interview, and documentation study. Then, the data were analyzed by interactive model analysis technique. The finding of this study indicated that (1) The implementation of Virtual Office Administration System (siMAYA) in West Sumatera Provincial Secretariat had not been effective; (2) There were still many inhibiting factors in the implementation of siMAYA program in West Sumatera Provincial Secretariat office, such as limited human resources, lack of hardware devices, unclear software usage, lack of data, and limited of LAN network. (3) Efforts made in overcoming these barriers include human resources training and completing the facilities and infrastructures.